The Ethiopian curriculum development and implementation vis-à-vis Schwab's signs of crisis in the field of curriculum - Solomon Melese; Aschale Tadege (Cogent Education, 2019)
A well-noted scholar in curriculum Joseph Schwab claimed that the field of curriculum in the US was in a state of decline by unexamined and mistaken reliance on theory specially in the 1960s. The main purpose of this paper is to analyze the Ethiopian practical experiences of curriculum development and implementation context with respect to Schwab's curriculum theory, with a focus on the crisis and renaissance of the curriculum field. To this end, different local researches, policy documents, discussion with ministry officials, and the researchers’ lived experiences were used as the sources of data. Integrated with data collection, reflection analysis was made in narrative basis. The paper suggests that the curriculum as a field is not well articulated, the six signs of crisis are existent, and the resolutions forwarded by Schwab are not in place in the Ethiopian curriculum development and implementation scenario. Accordingly, we recommended that genuine participation of key stakeholders is necessary to realize Schwab's deliberative curriculum development and implementation practices. To this effect, curriculum specialists should be organized and establish professional association aimed toward protecting the profession, safeguarding the field, providing consultation in curriculum planning, supervising school practices, and being engaged in any curriculum endeavors so that renaissance in the curriculum field will be ensured.